Contribution of Fatty Acid Amide Hydrolase to Alcohol Use Disorder: A Systematic Review - Niemela, Greta; Terry, Garth E (Cannabis and cannabinoid research, 2021)
Recent research has suggested that chronic alcohol exposure induces changes in the endocannabinoid system within the central nervous system and therefore could be an attractive target for better understanding and treating alcohol use disorder (AUD). Much of this research has centered around the CB receptor and its endogenous partial agonist, the endocannabinoid anandamide, as the CB receptor is densely expressed in brain regions involved in development and maintenance of addictive behaviors. In addition, recent evidence has suggested that chronic alcohol exposure induces changes in the modulation of endocannabinoid concentration and suggests that these changes may contribute to the motivation to abuse alcohol. Therefore, we performed a systematic literature review to evaluate how fatty acid amide hydrolase (FAAH), an enzyme that degrades anandamide, relates to the characteristics and biology of AUD, as well as how modulating FAAH through pharmacologic inhibition or genetic manipulation affects outcomes related to alcohol use and consumption. A search strategy was developed using the terms "endocannabinoids" or "drug delivery systems" and "alcohol dependence" or "alcohol use disorder" or "alcoholism" and "Fatty Acid Amide Hydrolase" and "FAAH" as text words and Medical Subject Headings (i.e., MeSH and EMTREE). We then used this search strategy on the electronic databases PubMed, Embase, and Web of Science. We found 224 records; after removing repeated records (37%), articles that did not fit the topic question (47%), or were not primary research (4%), we included 26 for qualitative synthesis (12%). The literature clearly suggests that FAAH has a role in the biology and characteristics of AUD. FAAH inhibition seems especially promising as a target for alcohol withdrawal as it may lead to a reduction in symptoms, including anxiety and a reduction of alcohol intake reinstatement. However, decreased FAAH may also lead to reduced sensitivity to alcohol along with increased preference and intake. Modulation of FAAH is promising for therapeutic intervention of AUD, but requires more research. Pre-clinical studies have indicated that FAAH inhibition may reduce withdrawal characteristics, but may also exacerbate other characteristics of AUD outside of that period.